Project Approach to Management Teams Formation at the Municipal Level - V. V. Priyatelev (Управленческое консультирование)
In the article, experiment of the Vologda Region on introduction of project approach in personnel policy when forming management teams at the municipal level is announced. The instrument of realization of this approach is one of regional personnel projects named “The Team of the Governor: municipal level”. Its main goal — to increase quality of management in local governments through development of administrative competences not only in certain heads, and in the whole management teams including various categories of participants of municipal community. The project history, its main objectives, stages, methods of realization and the achieved results are considered.